Kinetic Study and Cyclization of High Tacticity of Polyacrylonitrile Under Different Oxygen Supply Concentration - Zhang, Li; Liu, Zhiling; Dai, Yongqiang; Li, Qifang (Asian Journal of Chemistry, 2013)
Isotactic polyacrylonitrile with triad isotacticity of 0.53 was successfully synthesized by using dialkylmagnesium as initiator. The effects of oxygen concentrating on chemical evolutions and thermal properties of iso-polyacrylonitrile were studied by Fourier transform infrared spectroscopy and thermal gravimetric analysis at different concentration (0, 20, 50 and 80 vol. %). Activation energy of thermal stabilization was obtained under non-isothermal conditions by using iso-conversional methods. The results showed that the amount of un-cyclized nitrile groups increased with oxygen concentration. This indicated that the cyclization was affected by oxygen concentration. Two stages and a large residue mass of iso-polyacrylonitrile pyrolysis during oxidation were detected in the oxygen-containing atmosphere. The activation energies were calculated by Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) iso-conversional method under different oxygen concentration varying from 0 to 80 %.